Governance and accounting practices in the Fugger family firm at the beginning of the sixteenth century. (August 2019) - Baker, Charles Richard; Quéré, Bertrand P
This article discusses the governance and accounting practices of the Fugger family firm in the late fifteenth and early sixteenth century under the leadership of Jakob Fugger II (1459–1525; hereafter Jakob Fugger). The Fugger family firm engaged in numerous enterprises, primarily centered on textile trading, banking, and mining of silver and copper. The management of the firm required sophisticated governance and accounting practices, knowledge of which Jakob Fugger appears to have acquired during his residence in the Venetian Republic in the years 1473 through 1487. At that time, Venice was the most important trading and financial center in Europe. When Jakob Fugger returned to Augsburg, Germany in 1487, he modeled the governance and accounting practices of his firm after those of the Italian city-states and eventually expanded the operations of his firm into one of the most important banking houses in sixteenth-century Europe, with more than a dozen branches and a multinational presence.